1998
DOI: 10.1093/gerona/53a.1.b71
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Time to Instability in Posture

Abstract: Two experiments are reported that were set up to examine the spatial-temporal boundaries of postural instability in upright stance as a function of age (60-96 years) and postural conditions. Subjects stood on a force platform under different experimental conditions (vision/no vision and arms up/down) so that the effect of age on key dynamic properties of postural stability could be determined. The findings showed that the ratio of the area of the motion of the center of pressure to the area within the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 17 publications
6
68
1
1
Order By: Relevance
“…With increasing age, there is a decrease in sensory function (Wolfson et al, 1992;Era et al, 2006) and a decrease in muscle strength (Porter et al, 1995). Slobounov et al (1998) measured postural sway in older adults aged 67 to 92 years and found that postural sway, with eyes open and closed, increased with age, but was aŠected to a much greater extent when visual cues were removed. Hasan et al (1990) investigated changes in postural sway in women over the age of 65 during eyes open double stance, eyes open single stance, eyes closed double stance, and eyes closed single stance.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing age, there is a decrease in sensory function (Wolfson et al, 1992;Era et al, 2006) and a decrease in muscle strength (Porter et al, 1995). Slobounov et al (1998) measured postural sway in older adults aged 67 to 92 years and found that postural sway, with eyes open and closed, increased with age, but was aŠected to a much greater extent when visual cues were removed. Hasan et al (1990) investigated changes in postural sway in women over the age of 65 during eyes open double stance, eyes open single stance, eyes closed double stance, and eyes closed single stance.…”
Section: Discussionmentioning
confidence: 99%
“…Slobounov et al [29] subsequently built on this theoretical and empirical background and investigated the VTC in standing-still posture as a function of cohort group (60-69, 70-79, 80-89, and 90-96 years of age). The functional stability boundary for each participant was initially determined through having the individuals lean as far outward as they could in all directions without falling.…”
Section: Aging and The Time To Instability In Postural Controlmentioning
confidence: 99%
“…TtC has been used to assess postural stability in quiet stance conditions involving relatively small CoM velocities and accelerations. Some calculate TtC as the distance to the base of support boundary divided by the velocity of the center of pressure (CoP) (Van Wegen et al 2002;Hertel et al 2006;Hertel and Olmsted-Kramer 2007) or CoM (Forth et al 2007), while others also include CoP acceleration (Slobounov et al 1997;Slobounov et al 1998;Patton et al 2000;Slobounov et al 2006;Haibach et al 2007). Comparison of these methods by Haddad et al (2006) suggested that the addition of acceleration information might better represent static postural control.…”
Section: Introductionmentioning
confidence: 99%